Evaluasi Keandalan PLTA Bakaru - Akbar Tanjung; Arman Jaya; Suryanto Suryanto; Apollo Apollo (Politeknik Negeri Ujung Pandang, 2021)
One form of water energy utilization is done by building a Hydroelectric Power Plant (PLTA) in Indonesia, the Bakaru PLTA is one of the projects within PT. PLN (Persero). This project is a Hydro Power Plant Master project with a SULSELRABAR transmission located 246 km from the city of Makassar. The operation of the Bakaru hydropower system is certainly expected to work optimally, reliably and efficiently. Therefore, evaluation or data on the performance of the generator itself is needed. This study was conducted to determine the condition of the Bakaru hydropower plant based on the equivalent availability factor (EAF) and Net Capacity Factor (NCF) and Cost of Production (BPP). The data used is operating data on the Bakaru hydropower plant for 1 year. The data was obtained by using the documentation technique, while the data analysis was carried out using the Microsoft Excel program. After conducting research, it can be concluded that the condition of the Bakaru hydropower plant in 2017 is considered normal, seen from the EAF value reaching 94.15% and the average EFOR value of 2.4% with the number of Service Hours (SH) of 16,912.93 hours from 2 units. with the percentage of Service Hours to Period Hours reaching 96.53%. Meanwhile, the Net Capacity Factor of the Bakaru hydropower plant in 2017 reached 85.83%, with a total gross energy production of 945,372.50 MWh. This value exceeds the target that has been set.